Undang-Undang PKDRT dalam Perspektif Hadis - Ahmad Khairuddin Hairul Hudaya M. Noor Fuady (Muadalah, 2013)
To protect family members from violence, the government in particular has ratified the Act on the Abolition of Domestic Violence (PKDRT) in 2004. According to the Act, violence may cover four things: physical, psychological, economic and sexual violences. Islamic teachings, especially those derived from the hadith, already contained a number of provisions which provide protection for family members, particularly wives, as mentioned in the Domestic Violence Act. Prophet, for example, denounced those who hit their wives like beating slaves, forbade the insult of wife and the prostitution againts women slaves, and encouraged to fulfill economic rights of wives. However, not all categories of violence that exist in PKDRT and in hadith are shared the same. Some differences lie between the two, especially in relation to sexual violence against wives.